Transforming Education with AI: Teachers' Views, Challenges, and Pathways to Success - Jabeen, Ghousia; Goli, Gurunadham; ., Kafila; Babu, Ramesh (Journal of Engineering Education Transformations, 2025)
The aim of this study, intended to identify educators’ expectations and concerns concerning the advantages and limitations of applying artificial intelligence (AI) in the sphere of education. The results point out that there exist multitude of challenges that must be resolved in order to fully capitalize on AI based pedagogical technologies for learning processes. The research report of this study carried out a systematic review process in an attempt to identify knowledge, skills and attitude that the instructors require in the application of AI based schemes in a classroom. Designing the methodology for training teachers for the use of digital technologies in their teaching work and ensuring that these teachers are provided with adequate skills, as well as paying attention to the technical issues of the application of digital technologies in the practice of teachers, is now the primary conclusion of the work. It can be suggested that the results of this study can underline the significance of the effective professional development programs supported by students’ achievements along with ethical and/or privacy concerns. This might help the instructors to manage better the constantly changing nature of education fortified by the artificial intelligence.